(untitled) (Ustozlar uchun, 2025)
This article examines the fundamental theoretical frameworks used to analyze regional integration processes. It critically reviews classical, explicative, descriptive, prescriptive, and economic integration theories, highlighting their contributions and limitations. The study emphasizes the evolution from federalism and functionalism to neofunctionalism, communication theory, liberal intergovernmentalism, network approaches, new institutionalism, social constructivism, the legalist approach, and economic integration models.